The Magic - Byrne, Rhonda (London Simon & Schuster, 2012)
In The Magic a great mystery from a sacred text is revealed, and with this knowledge Rhonda Byrne takes the reader on a life-changing journey for 28 days. Step by step, day-by-day, secret teachings, revelations, and scientific law are brought together to form 28 simple practices that open the reader's eyes to a new world, and lead them to a dream life.
Includes Illustrations
Keywords: Beehives -- Gratitude -- Self-Realization